Constitutional Reinforcement of the Integration of Indonesian and Islamic Values - Mahfud MD, Moh.; Heryansyah, Despan (Universitas Islam Indonesia, 2025)
The importance of reaffirming the fundamental values of Indonesian arises from the emergence of issues such as radicalism, terrorism, intolerance, ethnicity, religious, racial, and intergroup-related conflicts, social and economic inequality, poor law enforcement and justice system, and many other social problems. This situation is further exacerbated by additional social, political, legal, and constitutional challenges. In addressing these issues, strengthening the rule of law based on the protection of human rights remains an imperative. However, reinforcing the fundamental values of Indonesian is equally crucial. Indonesian fundamental values are deeply rooted in and derived from the national identity of its people. This article focuses on three research questions. How to put religion and its values in the Indonesian fundamental values? How do Indonesian fundamental values deal with current political and legal turbulence? How does the implementation of Indonesian fundamental value pluralism in the legal system? This article is based on doctrinal research involving secondary data. This study found that Pancasila as the foundation of the state constitutes a modus vivendi or noble consensus, or mîtsâqon ghalîdzâ in a religious sense, so Indonesian Muslims should accept Pancasila as mîtsâqon ghalîdzâ. The strength of the national bond also stems from the commitment to the implementation of a unitary national law that is rooted in Pancasila, which generates hierarchical laws based on the 1945 Constitution of the Republic of Indonesia. As the state ideology, Pancasila constitutes the primary source of all legal sources. There should be no law conflicting with the precepts of Pancasila.